Determinants of injuries in passenger vessel accidents. (September 2015) - Yip, Tsz Leung; Jin, Di; Talley, Wayne K.
Highlights: We examine the determinants of crew and passenger injuries in passenger vessel accidents. Crew and passenger injury equations were estimated for ferry, ocean cruise, and river cruise vessel accidents using Poisson regressions. The results provide empirical evidence (for the first time in the literature) that crew injuries are determinants of passenger injuries in passenger vessel accidents. Abstract: This paper investigates determinants of crew and passenger injuries in passenger vessel accidents. Crew and passenger injury equations are estimated for ferry, ocean cruise, and river cruise vessel accidents, utilizing detailed data of individual vessel accidents that were investigated by the U.S. Coast Guard during the time period 2001–2008. The estimation results provide empirical evidence (for the first time in the literature) that crew injuries are determinants of passenger injuries in passenger vessel accidents.